Broadening the Picture of Short-Chain Acyl-CoA Dehydrogenase Deficiency: A Case Report with Microcephaly, Leukoencephalopathy, and Characteristic Magnetic Resonance Spectroscopic Findings - Papadopoulou, Maria; Papadopoulou-Legbelou, Kyriaki; Koutsampasopoulou, Iokasti; Tramma, Despoina; Evangeliou, Athanassios (Journal of Pediatric Neurology, 2018)
Short-chain acyl-CoA dehydrogenase deficiency (SCADD) is a mitochondrial fatty acid metabolism disorder, which results in the accumulation of butyrylcarnitine and ethylmalonic acid in blood and urine. Evidence of genotype/phenotype correlation and neuroimaging characteristics is limited compared with other inborn errors of metabolism. We report a male patient with SCADD who initially presented with seizures, metabolic acidosis, microcephaly, and developmental delay with gradual amelioration of most symptoms. MRI/MRS revealed extended multifocal leukoencephalopathy, disturbed myelination, and abnormal brain energy metabolism with low choline/creatine ratio, which indicate the need for MRI/MRS follow-up even for asymptomatic patients with SCADD.
Keywords: short-chain acyl-CoA dehydrogenase deficiency; microcephaly; leukoencephalopathy; magnetic resonance spectroscopy